Prevalence and factors associated with fragility syndrome in older adults attending the EsSalud primary health care service, January - April 2015. Chiclayo, Peru - Gonzáles-Mechán, Milton Carlos (2017)
Objectives: To identify the prevalence and factors associated with fragility syndrome in older adults attending the EsSalud (Peruvian Social Security Health Insurance) primary health care service, Chiclayo - Peru. Materials and methods: A descriptive, prospective and cross-sectional study was conducted on a sample consisting of 326 older adults from urban areas and surrounding districts of Chiclayo, who attend the outpatient service at the Hospital Naylamp and Policlínico Chiclayo Oeste. A data collection sheet including social-demographic variables, comorbidity and polypharmacy, and fragility syndrome clinical criteria was filled in. Results: The prevalence of fragility was 17.5% and that of pre-fragility, 40.9%. The most frequent fragility clinical criteria were as follows: self-reported fatigue (42.3%) and decreased grip strength (32.8%). The bivariate analysis showed an association with age, level of education, occupation (class IV and V concerning manual work), comorbidity (class II, asymptomatic disease or asymptomatic disease that requires medication but is under control), polypharmacy, anemia, Parkinson’s disease and non-vascular neurological disease. The final prediction model covering the age (1.08, 95% CI: 1.03 to 1.12), higher education level as a preventive variable (0.21, 95% CI: 0.07 to 0.62), type II comorbidity (11 08, 95% CI: 1.45 to 84.38) and polypharmacy (2.49, 95% CI: 1.24 to 5.03) predicts the likelihood of fragility syndrome in 75.6%. Conclusions: There is a high prevalence of fragility in the elderly population attending the primary health care service, and a significant association with age, higher education level, type II comorbidity and polypharmacy.